The Impact of Racial Disparities on Outcome in Patients With Stage IIIC Endometrial Carcinoma: A Pooled Data Analysis. (10th March 2023) - Patrich, Tomas; Wang, Yaqun; Elshaikh, Mohamed A.; Zhu, Simeng; Damast, Shari; Li, Jessie Y.; Fields, Emma C.; Beriwal, Sushil; Keller, Andrew; Kidd, Elizabeth A.; Usoz, Melissa; Jolly, Shruti; et al.
Abstract : Objective: To report the impact of race on clinical outcomes in patients with stage IIIC endometrial carcinoma. Materials and Methods: A retrospective multi-institutional study included 90 black and 568 non-black patients with stage IIIC endometrial carcinoma who received adjuvant chemotherapy and radiation treatments. Overall survival (OS) and recurrence-free survival (RFS) were calculated by the Kaplan-Meier method. Propensity score matching (PSM) was conducted. Statistical analyses were conducted using SPSS version 27. Results: The Median follow-up was 45.3 months. black patients were significantly older, had more nonendometrioid histology, grade 3 tumors, and were more likely to have >1 positive paraaortic lymph nodes compared with non-black patients (all P <0.0001). The 5-year estimated OS and RFS rates were 45% and 47% compared with 77% and 68% for black patients versus non-black patients, respectively ( P <0.001). After PSM, the 2 groups were well-balanced for all prognostic covariates. The estimated hazard ratios of black versus non-black patients were 1.613 ( P value=0.045) for OS and 1.487 ( P value=0.116) for RFS. After PSM, black patients were more likely to receive the "Sandwich" approach and concurrent chemoradiotherapy compared with non-black ( P =0.013) patients. Conclusions: Black patients have higher rates of nonendometrioid histology, grade 3 tumors, and number of involved paraaortic lymph nodes, worse OS, and RFS, and were more likely to receive the "Sandwich" approach compared with non-black patients. After PSM, black patients had worse OS with a nonsignificant trend in RFS. Access to care, equitable inclusion on randomized trials, and identification of genomic differences are warranted to help mitigate disparities.